Glycemic changes in women after gestational diabetes mellitus - Hellmann, Pâmella; Santana Trindade, Maria Aline; Domingues da Fonseca, Luiza; Baptistella do Nascimento, Iramar; Silva, Jean Carl (O Mundo da Saúde, 2019)
Gestational diabetes mellitus (GDM) is a glucose intolerance initially diagnosed throughout the 2nd and 3rd trimester of pregnancy. The purpose of this study was to estimate postpartum diabetes reassessment rates in women with GDM by identifying the persistence of glycemic changes and associated factors. The research is characterized as a retrospective cohort, investigating the postpartum follow-up data from 2010 to 2018. The mothers were divided into two groups: one with normal oral glucose tolerance tests (OGTT) and another group with abnormal tests. Subsequently, a comparison of variables between the two groups was performed considering: the average time for the development of GDM, maternal age, body mass index, gestational age at diagnosis, type of treatment used and postpartum return. Multinomial logistic regression calculations were performed. Data from 578 pregnant women were used and from these, 263 (45.50%) who returned after delivery were evaluated, 197 (74.90%) represented the normoglycemic group and 66 (25.09%) the group with glycemic changes. 41 (15.59%) had carbohydrate intolerance and 25 (9.5%) developed type 2 diabetes mellitus. There was no increased chance of altered OGTT postpartum with maternal ages >35 years, obesity and type of treatment used during prenatal care. Consecutively, the statistical data showed an increased chance of altered OGTT in the second trimester diagnosis of GDM (3.493% CI95% 1.570-7.770), and, concomitantly, glycosylated hemoglobin A1C fraction was >5.8 during prenatal care (3.014 CI95% 1.084-8.380). Moreover, the diagnosis in the third trimester was demonstrated as having a protective effect (0.484 95% CI 0.271-0.865). Less than 50% of the patients returned, and of these, 25% had altered OGTT. This study points to an increased risk of altered OGTT when GDM is diagnosed in the second trimester of pregnancy. Thus, a diagnosis in the second gestational trimester and a glycosylated hemoglobin fraction >5.8 increased the chances of altered OGTT, meanwhile, a diagnosis in the third trimester decreased the chances of OGTT alterations postpartum.